The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1021/bi962889v
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the DNA Polymerase α Associated Exonuclease:  The RTH1 Gene Product

Abstract: We report here the purification and mechanistic characterization of a 5'-3' exonuclease associated with DNA polymerase alpha from the yeast Saccharomyces cerevisiae. Earlier, we identified a 5' --> 3' exonuclease activity that copurified with yeast DNA polymerase alpha-primase in a multiprotein complex [Biswas, E. E., et al. (1993) Biochemistry, 32, 3020-3027]. Peptide sequence analysis of the purified 47 kDa exonuclease was carried out, and the peptide sequence was found to be identical to the S. cerevisiae g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…To date, nine different proteins involved in DNA metabolic pathways have been reported to interact with hFEN-1 nuclease. They include PCNA, APE-1, Dna2 helicase, RPA, replication factor C (RF-C), pol ␣, pol ␤, pol ⑀, and type II DNA topisomerase (13)(14)(15)(16)(17)(18). All of these proteins are essentially involved in two different general cellular processes, namely DNA replication and DNA base damage repair, which is consistent with the dual roles of hFEN-1 in DNA replication and repair.…”
supporting
confidence: 54%
“…To date, nine different proteins involved in DNA metabolic pathways have been reported to interact with hFEN-1 nuclease. They include PCNA, APE-1, Dna2 helicase, RPA, replication factor C (RF-C), pol ␣, pol ␤, pol ⑀, and type II DNA topisomerase (13)(14)(15)(16)(17)(18). All of these proteins are essentially involved in two different general cellular processes, namely DNA replication and DNA base damage repair, which is consistent with the dual roles of hFEN-1 in DNA replication and repair.…”
supporting
confidence: 54%
“…RTH1 nuclease possesses a RNase H activity that is most likely important in the maturation of Okazaki fragments in the lagging strand of the replication fork, similar to that observed with the 5′ f 3′ exonuclease activity of DNA polymerase I of E. coli (Kornberg & Baker, 1992). Earlier we have shown that RTH1 nuclease can degrade multimeric RNA primers synthesized by yeast pol R-primase complex (Zhu et al, 1997). Therefore, we have examined the effect of RPA on the RNase H activity of RTH1 nuclease.…”
Section: Native Rth1 Endonuclease Prefers Dna Substrates Having a Flamentioning
confidence: 99%
“…Earlier we have shown that a 5′ f 3′ exonuclease copurifies with DNA polymerase R-primase (pol R) complex (Biswas et al, 1993a). Purification of this nuclease from S. cereVisiae and determination of its identity as the RTH1 5′ f 3′ exonuclease have been described earlier (Zhu et al, 1997). The native RTH1 5′ f 3′ exonuclease also possesses a structure-specific endonuclease activity on forked DNA structures, in addition to its exonuclease and RNase H activities.…”
mentioning
confidence: 92%
“…Rad27, a fourth, related protein, is a structure-specific endoand exonuclease homologous to the human FEN-1 enzyme (5,21,31,42,51,55,71). Yeast cells carrying a null allele of the RAD27 gene display a broad array of defects in genome stability, including an elevated spontaneous mutation rate (64), expansion and contraction of micro-and minisatellite sequences (19,26,27,48,56), telomeric repeat fluctuation (40), increased spontaneous recombination (19,32,55,64,67), and increased chromosome breakage (19,67).…”
mentioning
confidence: 99%